PENGARUH PROGRAM CHARACTER BUILDING TERHADAP TINGKAT KEDISIPLINAN PESERTA DIDIK SMA NEGERI 3 BANYUASIN III - Endang Widawati (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2017)
School is one of education units which has a significant role in shaping and fostering the characters of the students. In order to develop the good characters of the students; the students who are well-behaved, have high integrity and discipline, SMAN 3 Banyuasin III hold a program which is called Character Building. This program has been held for 2 times starting from Academic Year 2015/2016. This program is a followed up activity from the point system which is applied in SMAN 3 BAnyuasin III. This study aims to find out how far the influence of the program in improving the discipline of the students in SMAN 3 BAnyuasin III. In the beginning, this program was followed by 22 participants, next it was followed by 16. The respondents of this study involved 22 people including teachers and students. The method used was qualitative study with purposive sampling. The data obtained through interview, observation and documentation. From the result of the interview, 77% of respondents said that the Character Building program was very effective in improving the disciplined character of the students at SMAN 3 Banyuasin III.